Cardiovascular risk factors in patients with chronic plaque psoriasis: a case-control study on the Brasov County population - Marius Irimie, Alexandru Oanţă, Claudia Alexandrina Irimie, Lazslo Gyula Fekete, Dan Ioan Minea, Alina Pascu (Zagreb : Hrvatsko dermatološko društvo hrvatskog liječničkog zbora, 2015)
Many studies have suggested that cardiovascular risk factors seem to be more common in patients with psoriasis than in the general population. In this study we aimed to determine the prevalence of cardiovascular risk factors in patients with chronic plaque psoriasis depending on the severity of disease. We conducted a prospective study in Braşov County (Romania) including 142 patients with chronic plaque psoriasis and disease duration of at least six months and 167 controls without psoriasis. The severity of psoriasis was assessed using the psoriasis area and severity index (PASI) score. Along with a thorough medical history and physical examination, serum lipid profile and fasting plasma glucose tests were carried out. The 10-year Framingham risk score (FRS) for general cardiovascular disease, which includes age, gender, total cholesterol, HDL-cholesterol, systolic blood pressure, smoking status, and diabetes mellitus, was applied. The severity of chronic plaque psoriasis was mild in 32 patients (22.53%) and moderate to severe in 110 patients (77.47%). We found a significant higher prevalence of metabolic syndrome in the patient group compared to controls. Individual components of metabolic syndrome like waist circumference, elevated triglycerides, reduced HDL-C, impaired fasting plasma glucose, and arterial hypertension were also more prevalent in patients than in controls. Mean triglycerides, total cholesterol, LDL-cholesterol and HDL-cholesterol levels were significantly raised in patients with psoriasis when compared to controls. The 10-year FRS was significantly higher in patients with psoriasis than in controls (8.36±5.75 vs. 6.61±4.13; P<0.001). FRS was higher in men (P=0.012) and in patients older than 50 years (P=0.008). According to the severity of psoriasis, FRS increases significantly from mild to moderate-to-severe psoriasis (6.82±4.48 to 8.8±6.71; P=0.003). Psoriasis, and especially moderate to severe psoriasis, seems to represent a risk factor for cardiovascular disease. Patients with psoriasis should be risk-assessed for cardiovascular diseases, and comorbidities should be actively managed.